Successful treatment with corticosteroids for refractory deterioration of cryptococcal meningitis with an increasing cryptococcal antigen titer. (February 2020) - Takahashi, Yoshiaki; Morimoto, Nobutoshi; Takamiya, Motonori; Morimoto, Mizuki; Mino, Satoshi; Kuramoto, Satoshi; Kawauchi, Masamitsu; Yokota, Kyoko; Abe, Koji
Highlights: Cryptococcal meningitis may be refractory, despite the recommended treatment. Our case of refractory cryptococcal meningitis was treated by corticosteroids. Corticosteroid may be useful for selected patients with cryptococcal meningitis. Abstract: We report a 55-year-old man with Cryptococcus neoformans meningitis who showed refractory deterioration twice with an increased cerebrospinal fluid cryptococcal antigen titer during the course of treatment. Although the initial deterioration was temporarily improved by placement of a ventriculoperitoneal shunt, he experienced deterioration again. However, he improved after administration of systemic corticosteroids. The present case suggests that systemic corticosteroid can be a choice of treatment to rescue immunocompetent patients with Cryptococcus neoformans meningitis and severe deterioration, even if cerebrospinal fluid analysis shows an increased cryptococcal antigen titer.